2005
DOI: 10.1038/nrm1645
|View full text |Cite
|
Sign up to set email alerts
|

Understanding alternative splicing: towards a cellular code

Abstract: In violation of the 'one gene, one polypeptide' rule, alternative splicing allows individual genes to produce multiple protein isoforms - thereby playing a central part in generating complex proteomes. Alternative splicing also has a largely hidden function in quantitative gene control, by targeting RNAs for nonsense-mediated decay. Traditional gene-by-gene investigations of alternative splicing mechanisms are now being complemented by global approaches. These promise to reveal details of the nature and operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
1,030
0
16

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,161 publications
(1,057 citation statements)
references
References 141 publications
11
1,030
0
16
Order By: Relevance
“…This is best demonstrated by genes in arthropods that contain both multiple MXE clusters (“multi‐cluster”) and large clusters with up to 53 MXEs such as in the Drosophila Dscam genes (Graveley et al , 2004; Pillmann et al , 2011). This is in strong contrast to mutually exclusive splicing in vertebrates as there is to date no evidence of multi‐cluster or higher order MXE clusters (Matlin et al , 2005; Pan et al , 2008; Wang et al , 2008; Gerstein et al , 2014; Abascal et al , 2015a,b). …”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…This is best demonstrated by genes in arthropods that contain both multiple MXE clusters (“multi‐cluster”) and large clusters with up to 53 MXEs such as in the Drosophila Dscam genes (Graveley et al , 2004; Pillmann et al , 2011). This is in strong contrast to mutually exclusive splicing in vertebrates as there is to date no evidence of multi‐cluster or higher order MXE clusters (Matlin et al , 2005; Pan et al , 2008; Wang et al , 2008; Gerstein et al , 2014; Abascal et al , 2015a,b). …”
Section: Resultsmentioning
confidence: 93%
“…Alternative splicing of pre‐messenger RNAs is a mechanism common to almost all eukaryotes to generate a plethora of protein variants out of a limited number of genes (Matlin et al , 2005; Nilsen & Graveley, 2010; Lee & Rio, 2015). High‐throughput studies suggested that not only 95–100% of all multi‐exon genes in human are affected (Pan et al , 2008; Wang et al , 2008; Gerstein et al , 2014) but also that alternative splicing patterns strongly diverged between vertebrate lineages implying a pronounced role in the evolution of phenotypic complexity (Barbosa‐Morais et al , 2012; Merkin et al , 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tight regulation of the expression of splicing factors is necessary for proper splicing outcomes (Matlin, Clark, & Smith, 2005; Shin & Manley, 2004), and splicing factors themselves exhibit altered patterns of age‐related splicing (Rodríguez et al, 2016). In our data, we observe age‐associated differential splicing of several splicing‐related genes including muscleblind ( mbl ) and Protein on ecdysone puffs ( Pep) .…”
Section: Discussionmentioning
confidence: 99%
“…Whereas genes are comprised of a relatively unvarying linear sequence of nucleotides, the proteins resulting from such genes are much more varied in structure, function and dynamic range (at least in our current understanding of gene regulation). This increased complexity is a result of alternative gene splicing (Matlin et al, 2005), post-translational modification (Walsh, 2006) and 'Omic' disciplines and systems biology in cattle breeding protein/protein interactions (Royer, 1999). Many hundreds of post-translational modifications exist including proteolytic cleavage, acylation, glycosylation, methylation, phosphorylation, sulfation, and di-sulfide bond formation (Krishna and Wold, 1998).…”
Section: Proteomicsmentioning
confidence: 99%